2015
DOI: 10.30970/sbi.0901.419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles on maturation of rabbit’s oocytes co-cultured with granulosa cells in vitro

Abstract: Silver nanoparticles are widely used in different fields of medicine despite the lack of information on their influence on animal's reproductive system, mammalian gametes and embryos. We investigated the effect of different concentrations of silver nanoparticles (0, 0.01, 0.1, 1 and 10 µg/mL) on maturation of rabbit's oocytes co-culture with granulosa cells in vitro. For this purpose, we synthesized small (11.28±0.32 nm) spherical silver nanoparticles with different composite agents: polyvinylpyrrolidone and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…SP may be able to reduce oxidative stress and thus prevent follicular atresia as a result of this property. Oocyte volume, its nucleus, and zona pellucida thickness: Changes in oocyte volume and nucleus in different types of ovarian follicles, as well as zona pellucida thickness were not significantly observed in any group compared with the control group, which was somewhat consistent with the results of Syrvatka et al (Syrvatka et al, 2015). But they disagreed with Shariatzadeh and Khagavi Jafarabad's results (Seyed Mohammad Ali Shariatzadeh & Khagavi Jafarabad, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…SP may be able to reduce oxidative stress and thus prevent follicular atresia as a result of this property. Oocyte volume, its nucleus, and zona pellucida thickness: Changes in oocyte volume and nucleus in different types of ovarian follicles, as well as zona pellucida thickness were not significantly observed in any group compared with the control group, which was somewhat consistent with the results of Syrvatka et al (Syrvatka et al, 2015). But they disagreed with Shariatzadeh and Khagavi Jafarabad's results (Seyed Mohammad Ali Shariatzadeh & Khagavi Jafarabad, 2018).…”
Section: Discussionsupporting
confidence: 65%
“…The non-toxic effect of silver nanoparticles on rabbit oocytes is also observed due to the presence of zona pellucida (Syrvatka et al, 2015). Recent, studies have shown that inhaled, ingested, or dermally absorbed nanoparticles can translocate through the circulatory system and accumulate in different reproductive organs and even can enter into ovarian theca and granule cells.…”
Section: Ovarian Steroidogenesismentioning
confidence: 99%